2020
DOI: 10.3390/ma13245818
|View full text |Cite
|
Sign up to set email alerts
|

The Friction-Induced Vibration of Water-Lubricated Rubber Bearings during the Shutdown Process

Abstract: The vibration noise generated by water-lubricated rubber bearings (WLRBs) seriously reduces the concealment of a ship’s navigation. The purpose of this study was to obtain the relationships between friction-induced vibration and the friction coefficient, specific pressure, temperature, and stiffness of the bearing support during the shutdown process of WLRBs. Using transient dynamic analysis (Abaqus/Standard), the shutdown process of the bearing system was simulated by setting a friction coefficient curve, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The variation of friction coefficient between the gate and track was weakened in this study, and the friction coefficient was viewed as a constant in the numerical model. In fact, the relationship between the friction coefficient and the relative velocity in the closing process should be taken into account, which involves the study of the friction mechanism [30,31]. Thus, the relationship and distinction of the friction-induced vibration and flow-induced vibration in the closing process need to be given more attention in subsequent research.…”
Section: Factor Analysismentioning
confidence: 99%
“…The variation of friction coefficient between the gate and track was weakened in this study, and the friction coefficient was viewed as a constant in the numerical model. In fact, the relationship between the friction coefficient and the relative velocity in the closing process should be taken into account, which involves the study of the friction mechanism [30,31]. Thus, the relationship and distinction of the friction-induced vibration and flow-induced vibration in the closing process need to be given more attention in subsequent research.…”
Section: Factor Analysismentioning
confidence: 99%
“…Zhou et al investigated the relationships between the friction coefficient, specific pressure, temperature, and hardness of vibration noise produced by water-lubricated NBR rubber bearings (WLRB) by using temporal dynamic analysis (Abaqus/Standard). The results showed that proportionally increasing the coefficient of friction and specific pressure caused higher vibrations and the effect of specific pressure on vibration was more pronounced than the coefficient of friction [21]. Zhao and Zhang carried out theoretical analysis and experiments with the finite difference method to determine the hydrodynamic properties of water-lubricated plain bearings in their study and determined that when the speed is increased, the hydrodynamic effect is obvious, and the water film is discontinuous at speeds lower than 1800 rpm [22].…”
Section: Introductionmentioning
confidence: 99%
“…Oil-lubricated stern bearings have the risk of oil leakage and combustion in the process of use and are prone to wear and damage due to dry friction when the oil is cut off [1]. With growing environmental awareness and stricter pollution standards, people are urged to research and develop new bearing systems that are pollution-free, wear-resistant, efficient, energy-saving, long-lasting, and so on [2][3][4]. Water is the most promising lubricating medium due to its non-pollution, wide source, safety, and incombustibility properties [5,6].…”
Section: Introductionmentioning
confidence: 99%